Comparison of Factors of Stress among Women Entrepreneurs in Different Types of Business (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The characteristics of men and women entrepreneurs are generally very similar. The differences are found onlyin age, personality, motivation and type of business started. Women are by and large born managers as theymanage their home. They can do simultaneously do more than one task at a time and have good coordinationskills. They invariably think of entering a business once their children are grown up and householdresponsibilities get reduced. Women were subjected to greater stress as the demands, expectations from homeand career at times caused greater conflicts which strives for multi role duties and it results in stress,ambivalence and overload which may leads to low work life balance. This article not only discuss about thefactors of stress in different types of businesses but also the methods to cope up with stress. Further it is alsocompared the factors of stress among Women Entrepreneurs in manufacturing, service and trading.